Selective populations of hippocampal interneurons express ErbB4 and their number and distribution is altered in ErbB4 knockout mice - Neddens, Jörg (2010)
Neuregulins (NRGs) are ligands of ErbB receptor tyrosine kinases. The NRG1-ErbB4 pathway has been shown to modulate hippocampal synaptic plasticity and network oscillations in the adult rodent brain. In order to identify cells that mediate these effects here we determine the expression pattern of ErbB4 in four functionally distinct classes of interneurons that represent the majority of all inhibitory neurons in the hippocampus. Based on data from 15 mice and 25,000 cells, we show that ErbB4 is expressed in cells that are positive for cholecystokinin (CCK, 54%), parvalbumin (PV, 42%), or neuronal nitric oxide synthase (nNOS, 39%) in a layer-specific and region-specific manner, whereas cells expressing somatostatin (SOM) are rarely immunoreactive for ErbB4 (1%). We next compared the numerical density (cells/mm(3)) and the distribution of interneurons between ErbB4−/− mice and wildtype controls. Based on data from 25 mice and 56,000 cells, we detected reductions of PV-positive and nNOS-positive cells in knockouts (−24% and −27%, respectively) but only a minor reduction of CCK-positive cells; no changes in SOM-positive cells were observed. The overall reduction of interneurons was verified by quantification of GAD67-immunoreactive cells (−24% in ErbB4−/− mice). The reduction of interneurons along the dorsoventral axis was more severe in intermediate and ventral portions than in the dorsal hippocampus, and regional reductions occurred in the CA1-3 regions and subiculum, whereas we found no significant changes in the dentate gyrus. The expression by different populations of interneurons suggests that ErbB4 can modulate several microcircuits within the hippocampus and mediate the previously reported effects of NRG1 on network oscillations and synaptic plasticity. The selective reduction of GABAergic cells in ErbB4−/− mice is consistent with the role of NRG-ErbB4 signaling in the generation and migration of interneurons during development, and with neuronal and behavioral functional deficits in adult ErbB4 knockouts.